AN ANALYSIS OF THEACHER QUESTIONING STRATEGIES IN THE CLASSROOM INTERACTION OF SPEAKING CLASS AT GRADE XI SMA MUHAMMADIYAH TEMBILAHAN - Fitri; Maizarah; Syafrizal (J-Shelves of Indragiri (JSI), 2022)
The research aimed to find out the questioning strategy used by the teacher in teaching speaking in the classroom interaction at SMA Muhammadiyah Tembilahan and to examine the function of the questions applied by the teacher. The research design in this study was descriptive-qualitative. The sample for this research was the English teacher. The research used total sampling by using one teacher as a participant. To get the data, the researcher used a questionnaire and an interview. According to the data analysis, the teacher employed several strategies, including wait time, repetition, paraphrasing, simplification, and probing strategy. The questionnaire and interview demonstrated that the teacher had a good interaction with the students using questioning strategies, and both the teacher and the student agreed that questioning strategies could help students understand the material.